Spatiotemporal choreography of chromosome and megaplasmids in the Sinorhizobium meliloti cell cycle. Issue 5 (20th April 2016) - Frage, Benjamin; Döhlemann, Johannes; Robledo, Marta; Lucena, Daniella; Sobetzko, Patrick; Graumann, Peter L.; Becker, Anke
Summary: A considerable share of bacterial species maintains multipartite genomes. Precise coordination of genome replication and segregation with cell growth and division is vital for proliferation of these bacteria. The α‐proteobacterium Sinorhizobium meliloti possesses a tripartite genome composed of one chromosome and the megaplasmids pSymA and pSymB. Here, we investigated the spatiotemporal pattern of segregation of these S. meliloti replicons at single cell level. Duplication of chromosomal and megaplasmid origins of replication occurred spatially and temporally separated, and only once per cell cycle. Tracking of FROS (fluorescent repressor operator system)‐labelled origins revealed a strict temporal order of segregation events commencing with the chromosome followed by pSymA and then by pSymB. The repA2B2C2 region derived from pSymA was sufficient to confer the spatiotemporal behaviour of this megaplasmid to a small plasmid. Altering activity of the ubiquitous prokaryotic replication initiator DnaA, either positively or negatively, resulted in an increase in replication initiation events or G1 arrest of the chromosome only. This suggests that interference with DnaA activity does not affect replication initiation control of the megaplasmids. Abstract : A considerable share of bacterial species maintains multipartite genomes. The alpha‐proteobacterium Sinorhizobium meliloti possesses a tripartite genome composed of one chromosome and the megaplasmids pSymA and pSymB. Monitoring the spatiotemporal dynamics of the origins of replication of these replicons revealed a strict temporal order of segregation events commencing with the chromosome followed by pSymA and then by pSymB.